Ciało obce wewnątrzoczodołowe – 3-letnia obserwacja - Jędrzejewski, Wojciech; Herba, Ewa; Pojda-Wilczek, Dorota; Pojda, Stefan (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
A case of patient with metallic intraorbital foreign body, was described. The foreign body went trough the eye and finally was situated close to the optic nerve. After three years, no signs of siderosis were found (ERG). The patient is still under control.